IMPLEMENTASI PLUGIN MATHJAX UNTUK MENAMPILKAN EQUATION INTERAKTIF PADA MEDIA PEMBELAJARAN MATEMATIKA BERBASIS WEB MENGGUNAKAN CMS WORDPRESS - Suendri S; Nanda Novita (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The development of modern Information Technology has greatly changed the paradigm of the delivery of learning materials to learners, ranging from changes in methods that make teachers no longer as the only source of information to the use of learning media using the internet. One of the Content Management System that has been available for free that is easy to use in the medium of learning via the internet is WordPress. While the plugin used to display Math notation is Mathjax. MathJax is a plugin created by the American Mathematical Society (AMS) and the Society for Industrial and Applied Mathematics (SIAM) aimed at displaying high quality math and scientific notations that can run on all browsers. support for LaTeX, MathML and other equations markup directly in the HTML source. an extensible, modular design with a rich API for easy integration into web applications.